Learning from scripts to communicate using geographic maps: Institutional visual culture of backlands and conquered borders (18th century) - de Moura, Denise A.S. [UNESP] (Instituto Colombiano de Antropologia e Historia (ICANH), 2021)
Backwoodsmen and missionaries in 18th century America continued a Castilian tradition of visual culture based on sketches, itinerary drawings, and maps that communicated their sense of space, the territory, and the places linked to their memories. With the political weight achieved by maps during this period due to the disputes for the definition of the Iberian territorial limits, the Portuguese Crown was faced with the need to overcome its deficient condition regarding the mapping of its interior lands. To this end, the Crown mobilized governors who in addition to implementing policies for mapping the territory also developed an institutional visual culture that appropriated the geographic knowledge generated by Jesuits' maps and cartography, using these assets to make their own cartographic images and represent and communicate areas and backlands as part of an imperial agenda toward the conquered territories and borders, as depicted in the official correspondence and maps of the time.
Aprendendo com roteiros a comunicar por carta geográfica: Cultura visual institucional de sertões e fronteiras conquistadas (século XVIII)
Keywords: Communication; Communication policy; Communication strategies; Maps; Visual materials; Visualization